Vers une cartographie systématique en diachronie de la recherche en prononciation de l’anglais L2 - Saandia Ali; Marie Garnier; Linda Terrier (Anglophonia)
This article introduces the initial results of a scoping review of research in L2 English pronunciation. The review is part of the open science and evidence-based teaching movements, in the context of the emergence of the intelligibility paradigm as a foil to the native model paradigm.The overall corpus of our scoping review includes 485 articles published from 1995 to 2020 included, and which document experimental research on L2 English pronunciation. These articles come from 35 major journals in the fields of phonology/phonetics (PHON), second language acquisition (SLA), and second language learning and teaching (SLLT). These sources are international journals published online and in English. In this paper we present the initial results of the review for the years 1995-1996, 2007-2008 and 2019-2020, accounting for a total of 117 articles. Three aspects are the focus of this review: the speakers and listeners participating in the experiments, the phonological aspects the research focuses on, and the extent to which the intelligibility construct is taken into account in those studies.Our review shows that the number of speakers participating in the experiments has increased, even though the use of a large number of participants is still rare. The number of listeners participating in the experiments has increased sharply. The native standard remains an important reference point, especially in the PHON domain. Nevertheless, there has been a growing interest towards studying communication situations between non-native speakers and non-native listeners only, away from any reference to the native standard. Among the studies dealing with phonological aspects, a majority focuses on segmental features, although the consideration of suprasegmental aspects has increased between 1995 and 2020, especially regarding the temporal characteristics of the speech signal. Articles on segmental features most often deal with specific consonant clusters or a set of minimal pairs relevant to the learners featured in the study rather than with the production of a particular segment. Finally, there has been a rise in the proportion of articles taking into account the intelligibility construct between 1995 and 2020, with a bump in interest for research focused on this construct in the mid-2000s. More articles taking intelligibility into account are published in the PHON domain (71%) than in the SLA/SLLT domain (58%).